Kephalaia 55 and the Great Free Woman: Concepts of Seclusion and Public Exhibition in Relation to Women and Female Figures in Manichaean Texts - Franzmann, Majella (Koninklijke Brill NV, 2015)
One of the key moments in the Manichaean drama of salvation concerns the event known generally as the seduction of the archons. In one of the many narrations of this event in Chapter 55 of the Kephalaia, we are presented with a central woman character for whom seclusion from the public gaze appears to be the norm in her daily life, and yet who uncharacteristically and deliberately exhibits herself in public. In this study I begin from that story in the Kephalaia and attempt to situate the depiction of the woman character within the broader Manichaean teaching about, and portrayal of, women and female characters in both private and public spaces, as well as situating the story within other versions of the event of the seduction of the archons.